ANALISIS KEPADATAN LALAT (MUSCA DOMESTICA) DAN KONDISI MIKROKLIMAT PADA TEMPAT PENAMPUNGAN SEMENTARA (TPS) SAMPAH KOTA SAMARINDA - Muhammad Aidil Fitrah; Morrin Choirunnisa Thohira (Jurnal Sanitasi Profesional Indonesia, 2026)
Temporary Waste Storage Sites (TPS) are potential breeding grounds for house flies (Musca domestica) due to the accumulation of organic waste and inadequate sanitation conditions. High fly density may increase environmental health risks because flies act as mechanical vectors of various pathogenic microorganisms. This study aimed to analyze fly density and microclimatic conditions, including temperature and humidity, at TPS locations in Samarinda City. A quantitative analytical study with a cross-sectional design was conducted in March 2026 at eight active TPS locations selected purposively. Fly density was measured using the fly grill method according to the Indonesian Ministry of Health guidelines, while temperature and humidity were recorded using a hygrometer. The results showed that the average fly density index ranged from 7.8 to 40.2 flies per fly grill, indicating high to very high density levels at all observation sites. The highest density was observed at TPS Gang Ayu (40.2 flies/fly grill), while the lowest was found at TPS Kontainer Statis Air Putih (7.8 flies/fly grill). Environmental conditions showed temperatures ranging from 27.8°C to 35.9°C and humidity levels between 48% and 70%, which are favorable for fly survival and reproduction. However, fly density variations were not solely influenced by microclimatic factors but were also associated with waste volume, waste accumulation duration, transportation frequency, and sanitation conditions. In conclusion, fly density at TPS in Samarinda City remains high and poses potential environmental health risks. Improved waste management, routine sanitation measures, and continuous fly density monitoring are recommended to reduce vector populations and minimize disease transmission risks.